The Indonesias state budget sustainability and its implication for financial system stability - Haryo Kunvoro (Romanian Journal of Fiscal Policy (RJFP), 2011)
This paper will examine the sustainability of the central budget and its relation to the financial stability in the case of Indonesia. The standard model of fiscal sustainability is modified to cover some financial variables. The empirical estimates are done by employing several aspects of the time series econometric literature including unit roots, co-integration, and VAR (vector auto regression). Based on the fiscal reaction function estimates of quarterly data over the period of 1999-2009, the analysis present that the government's budget is unsustainable. This finding is supported by solvency test. The impulse response test indicates that financial variables innovation has large impact both on the debt and primary balance surplus dynamics and vise versa. Eventually, the debt and primary balance have a substantial impact on financial system. Thus, the fiscal sustainability (and, of course, solvency) is the key to achieve financial system stability.
Keywords: E62; H62; H63; H68; 330; debt; primary Balance; fiscal sustainability; financial stability; VAR